Practice activities and behaviours employed by youth soccer coaches within a professional female soccer academy in England: A case study - Alder, S. E.; McRobert, A. P.; Champ, F. M.; Causer, J.; Andrew, M. (International Journal of Sports Science & Coaching, 2025)
Previous research investigating the microstructure of practice activities and coach behaviours pre-date or coincide with the professionalisation of female soccer within England in 2018. Following substantial structural developments at youth level, an examination of these aspects within the female soccer context has become essential for supporting youth development. A case study approach was adopted to explore practice structure, coaching behaviours, and the rationale for their use within sessions. Fourteen youth soccer coaches and the Academy Director from a single Category 1 soccer academy within England participated. Systematic observations of activities and behaviours within practice sessions were conducted and analysed using a computerised coding program, followed by individual video feedback sessions and stimulated recall interviews with each coach. Coaches predominantly used games-based (54.3%) over drill-based activities (23.6%) within their sessions, which was consistent across all age categories (U10-U16), and was influenced by coach education, individual coaching styles and the environment created and managed by the academy director. Transition periods between activities were perceived as excessive (22.1%) but varied between age categories. High levels of instruction and praise were provided to maintain an intense and positive learning environment, whereas some coaches utilised silence to promote autonomous learning, reflecting varied coaching styles. Dual-coaching also effectively ensured players were engaged and appropriately challenged. This study provides contemporary data on coaching practice activities and behaviours to extend existing knowledge. It also explores these aspects in female soccer for the first time, offering practical implications for coaching.